IMPLEMENTASI NILAI-NILAI PEMBELAJARAN AKIDAH AKHLAK DALAM BUDAYA “MAPPATABE” PESERTA DIDIK KELAS VII MTsS PALATTAE KECAMATAN KAHU KABUPATEN BONE - Syahrul; Ali Akbar; Muhammad Rusmin B; Sitti Nadirah; Alamsyah Halim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the planning, implementation, and evaluation of the values ​​of aqidah akhlak learning in the “mappatabe” culture for grade VII students of MTsS Palattae, Kahu District, Bone Regency. This study uses a qualitative descriptive approach. Data were obtained through observation, interviews, and documentation with the aqidah akhlak teacher and grade VII students. The results of the study indicate that the planning was carried out systematically by integrating the values ​​of sipakatau (humanizing each other), sipakalebbi (respecting each other), and sipakainge (reminding each other) into the 5S habituation (smile, greeting, politeness, greeting, courtesy) in the madrasah. Implementation is carried out through teacher role models and habits, such as greeting, speaking politely, asking permission, and respecting others both inside and outside the madrasah. Evaluation is carried out continuously by emphasizing the affective and psychomotor aspects through direct observation, attitude journals, self-assessment, and peer assessment. This finding confirms that integrating learning of faith and morals with local cultural values ​​is able to shape the character of students who are polite, disciplined, and care about others